An Experimental Investigation on the Effects of the Base Fluid of External Fluid and Voltage on the Milling Performance of Nanofluid Composite Electrostatic Spraying - Yu Su; Qingxiang Yang; Pan Liu; Jiaxi You (Lubricants, 2023)
Nanofluid composite electrostatic spraying (NCES) is a new clean machining technology for minimum quantity lubrication. The base fluid of external fluid and voltage are the two important parameters that affect its performance. This study presented the effect of base fluid of external fluid on milling force and temperature of NCES to determine the suitable base fluid and the best external/internal fluid. Herein, castor oil, castor oil-based nanofluid, sunflower oil, and sunflower oil-based nanofluid were employed as external fluid, and water and water-based nanofluid as internal fluid. Atomization experiments were conducted to determine the common voltage for different external/internal fluids to generate an applicable atomization mode. Under this voltage, morphology of applicable atomization mode, current and standard deviation, droplet speed, and electrowetting contact angle were explored to discuss the effect of base fluid on NCES milling. Next, the best external/internal fluid was used to further investigate the milling force and temperature under various voltages. Sunflower oil was the suitable base fluid for NCES, and sunflower oil-based nanofluid/water-based nanofluid was found to be the best external/internal fluid causing a significant reduction in force and temperature. Compared to castor oil, sunflower oil as the base fluid lowered the milling force and temperature by 5.4–10.8% and 6.3–7.9%, respectively. Within the voltage range of applicable atomization mode, raising the voltage lowered the milling force and temperature by 2.4% and 3.9%, respectively.